PENGENALAN DESIGN SYSTEM DENGAN FIGMA SEBAGAI UPAYA PENINGKATAN KOMPETENSI DESAIN DIGITAL SISWA REKAYASA PERANGKAT LUNAK DI SMK AL AMANAH KOTA TANGERANG SELATAN - Muhammad Ilham Darmawan; Adelia Friskan Dita; Faisal Saputra; Linus Fister Waruwu; Muhammad Maula Albi B.; Meilandri Maulana; Muhammad Faisal Tanjung; Refaldo Wijaya; Rival Ardhita Ma’ruf; Okky Prasetia (Abdi Jurnal Publikasi, 2026)
The rapid development of digital technology demands the enhancement of systematic and professional interface design competencies, particularly for vocational high school students majoring in Software Engineering. One effective approach in digital design development is the use of a structured and consistent design system. This activity aims to introduce the concept of design systems and their implementation using Figma as an effort to improve the digital design competencies of Software Engineering students at SMK Al Amanah, South Tangerang City. The implementation method includes theoretical material delivery, demonstrations of Figma usage, and hands-on practice in developing a simple design system comprising color schemes, typography, icons, and user interface components. The results indicate that students gained a better understanding of the importance of design consistency and were able to apply design systems in designing application interfaces. In addition, the activity enhanced students’ skills in utilizing Figma as a collaborative design tool. Therefore, the introduction of Figma-based design systems can serve as an effective means of improving students’ digital design competencies and supporting their readiness to meet the demands of the information technology industry.